High-accuracy positioning for 5G-Advanced wireless systems - Bin REN; Zhenyu ZHANG; Rongyi FANG; Xiaotao REN; Jianxiang LI; Yunjing HOU; Zhe YU; Shaohui SUN (Dianxin kexue)
With the rapid development of positioning technology, high-accuracy positioning technology for 5G-Advanced is receiving more and more attention.Firstly, the current situation of 5G positioning standards based on the 3rd Generation Partnership Project (3GPP) Release 16/ Release17 and the enhancement directions of the 5G-Advanced positioning technology based on 3GPP Release 18 were introduced.Secondly, the 5G orthogonal frequency division multiplexing (OFDM) signal model and three key algorithms for carrier phase positioning technology were mainly studied, including: carrier phase measurement algorithm based on phase locked loop, double-difference algorithm based on reference user equipment (UE), and UE position calculation algorithm based on extended Kalman filter.Finally, the low-power high-accuracy positioning technology and the positioning accuracy enhancement technology based on positioning reference unit were analyzed.